Development of analytical models for confined masonry walls based on experimental results in Lima city - Diaz, Miguel (2019)
For 30 years the Structural Laboratory of the Peru Japan Center for Earthquake Engineering Research and Disaster Mitigation (CISMID) from the Faculty of Civil Engineering (FIC) of the National University of Engineering (UNI) is been testing different types of structural system, mainly confined masonry walls. In that sense, large number of experiments have been conducted in confined masonry walls. Analytical model for capacity curve is presented for walls with different types of masonry units, such as industrial hollow bricks, solid handmade bricks and tubular bricks which are the most representative units in Metropolitan Lima and Callao. Tetra-linear models are calibrated with experimental results in order to provided generalized model in terms of sensitive parameters which determines the capacity curve for flexural shear failure mechanism, such as longitudinal and transversal steel ratio, slenderness ratio and axial load ratio where shear stress is observed in the cracking, yielding, maximum and ultimate points.